Pengaruh Pecahan Batu Alam Andesit Sebagai Subtitusi Agregat Kasar Pada Beton Berongga - Bobby Adianto Rima; Benny Kusuma; Luciana Buarlele (Paulus Civil Engineering Journal, 2023)
Andesite natural stone is a porphyritic rock formed by volcanic eruptions and is gray-black in color with fine grains. The purpose of this study was to find out how crushed natural andesite affects coarse aggregate substitution The test material used in this experiment was a cylinder with a diameter of 15 cm and a height of 30 cm, and a cylinder of 10 cm x 20 cm. During 28days, concrete with a design compressive strength of 20MPa was tested for permeability, pore volume, and compressive strength in this study. The results showed that the compressive strength was affected by differences in the proportions of andesite found in nature. The compressive strength value decreases with the variation of the proportion while the pore volume and permeability increase.